Lymphatic regeneration after implantation of aligned nanofibrillar collagen scaffolds: Preliminary preclinical and clinical results. Issue 2 (21st September 2021) - Nguyen, Dung; Zaitseva, Tatiana S.; Zhou, Anna; Rochlin, Danielle; Sue, Gloria; Deptula, Peter; Tabada, Peter; Wan, Derrick; Loening, Andreas; Paukshto, Michael; Dionyssiou, Dimitrios
Abstract: Background: We tested our hypothesis that implantation of aligned nanofibrillar collagen scaffolds (BioBridge™) can both prevent and reduce established lymphedema in the rat lymphedema model. Our authors report clinical cases that demonstrate new lymphatic formation guided by BioBridge™ as seen by near‐infrared (NIR) fluoroscopy and magnetic resonance (MR) lymphography. Methods: A rat lymphedema model was utilized. A prevention group received implantation of BioBridge™ immediately after lymphadenectomy. A lymphedema group received implantation of BioBridge™ with autologous adipose‐derived stem cells (ADSC; treatment group) or remained untreated (control group). All subjects were observed for 4 months after lymphadenectomy. The hindlimb change was evaluated using computed tomography‐based volumetric analysis. Lymphagiogenesis was assessed by indocyanine green (ICG) lymphography. Results: Animals in the treatment group showed a reduction in affected limb volume. Animals in the prevention group showed no increase in the affected limb volume. ICG fluoroscopy demonstrated lymph flow and formation of lymphatics toward healthy lymphatics. Conclusions: In the rat lymphedema model, implantation of BioBridge™ at the time of lymph node removal prevents the development of lymphedema. Treatment of established lymphedema with the BioBridge™ and ADSC reduces lymphedema. New lymphatic vessels are demonstrated by NIR fluoroscopy and MR lymphography. These findings have implications for the treatment of lymphedema in human subjects.